The role of determining the borders in Kazakhstan ethnic integration (fully revised version) (Journal of Philosophy Culture and Political Science, 2019)
This article describes the history of the borders of Central Asia in 1924, whose history became popular and began after the dissolution of the interim government. This policy has influenced Kazakhstan. As a result of this policy, the ethnic composition of the territory of Kazakhstan was changed, and the size of the modern territories was determined. Currently, the Republic of Kazakhstan is a multinational state thanks to this policy. The purpose of the article is to study the influence of the formal border security policy on the ethnic composition of Kazakhstan. In the study of research works used archival materials of Russia, Uzbekistan and our country. The main events of the identification of the boundaries of 1924 related to cultural integration and its origin are determined. It also speaks of intellectuals and leaders of free people who were active in border. This topic has not previously been widely studied by science,and foreign literature on this topic has not been written. Because archival documents were available onlyafter independence. The article discusses issues of census and changes in the proportion of the localpopulation. Since the 1990s, political science has been part of the history department; over the years ofindependence, historians have begun to use their political views more closely.Key words: definition of borders, Central Asia, political intervention, political factors.